Incidencia del consumo de drogas y estupefacientes en el rendimiento académico de los estudiantes del primero de bachillerato en la Unidad Educativa Fiscal Santo Domingo De La Ciudad De Santo Domingo De Los Colorados, Cantón Santo Domingo De Los Colorados, Provincia de Los Tsáchilas - Moreira Párraga, Javier Antonio (2019)
The present investigation was carried out in the Educational Unit "Santo Domingo de los Colorados", Santo Domingo canton, Tsáchilas province. The main objective was to analyze the risk factors that affect the consumption of drugs and narcotics in students of the first year of high school. The research design is mixed, the population corresponds to 27 baccalaureate teachers, 80 students and 80 parents. A survey designed for this purpose was used as a data collection instrument. The work has interest, relevance and relevance, it was concluded that there are cases of students who use drugs and have done so within the educational institution said students come from dysfunctional homes, hence the proposal addressed to parents and students of the Fiscal Education Unit "Santo Domingo" through recreational activities to promote self-esteem and the cultivation of social values so as not to fall into the consumption of drugs and narcotics